KAJIAN PENGGALAN JALAN MT.HARYONO SEBAGAI SALAH SATU PENGEMBANGAN PUSATKOTA SEMARANG - Mira Dharma Susilawaty (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2010)
Various daily activities that happen at the street of MT. Haryono cause manyproblems to the city of Semarang. These problems include problems associated with theinterface system (linkage system), open space and green space systems, buildings layout,signal system, streetscape, city architecture, street vendors and informal sectors, as well asinfrastructure and utility systems.This study onMT.Haryono Streetwas aimed to analyze related problems that exist inthe surrounding urban areasusing direct observationson the regions, which are then comparedwith the existing urban theory appropriate to the circumstances of the area.These problems include linkage system, open space systems, buildings layout, andsignal and streetscape system.In order to support and encourage the development of the area as the city centre, anintegrated and thorough planning is necessary that covers all aspects of the existing conditionsof the MT.Haryono street so that the area will be functioning well as expected.Key words: urban problems. area development. city centre.